Moss stomata in highly elaborated Oedipodium (Oedipodiaceae) and highly reduced Ephemerum (Pottiaceae) sporophytes are remarkably similar1. Issue 12 (1st December 2013) - Merced, Amelia; Renzaglia, Karen S.
Abstract : Premise of the study: Mosses are central in understanding the origin, diversification, and early function of stomata in land plants. Oedipodium, the first extant moss with true stomata, has an elaborated capsule with numerous long‐pored stomata; in contrast, the reduced and short‐lived Ephemerum has few round‐pored stomata. Here we present a comparative study of sporophyte anatomy and ultrastructure of stomata in two divergent mosses and its implications for stomata diversity and function. Methods: Mature sporophytes of two moss species were studied using light, fluorescence, and scanning and transmission electron microscopy. Immunolocalization of pectin was conducted on Oedipodium using the LM19 antibody. Key results: Oedipodium capsules have extensive spongy tissue along the apophysis, whereas those of Ephemerum have minimal substomatal cavities. Stomatal ultrastructure and wall thickenings are highly similar. Sporophytes are covered by a cuticle that is thicker on guard cells and extends along walls surrounding the pore. Epicuticular waxes and pectin clog pores in old capsules. Conclusions: Ultrastructure of stomata in these mosses is similar to each other and less variable than that of tracheophytes. Anatomical features such as the presence of a cuticle, water‐conducting cells, and spongy tissues with large areas for gas exchange are more pronounced in Oedipodium sporophytes and support the role of stomata in gas exchange and water transport during development and maturation. These features are modified in the reduced sporophytes of Ephemerum . Capsule anatomy coupled with the exclusive existence of stomata on capsules supports the concept that stomata in moss may also facilitate drying and dispersal of spores.